Global Transcriptome Profiling Analysis of Inhibitory Effects of Paclobutrazol on Leaf Growth in Lily (Lilium Longiflorum-Asiatic Hybrid) - Zhu, Xiaopei; Chai, Min; Li, Yang; Sun, Meiyu; Zhang, Jinzheng; Sun, Guofeng; Jiang, Chuangdao; Shi, Lei (Frontiers in Plant Science, 2016)
As a popular ornamental flower, potted lily is an important object of lily breeding. Paclobutrazol, a chemical growth retardation compound, is often used to dwarf plant in producing potted lilies. However, in recent years, the plants with inherited dwarf traits by using genetic engineer breeding technology are being developed. The studies on molecular basis of lily dwarfism will offer some target genes which have profound dwarf effect for genetic engineer breeding. Here, we confirmed that paclobutrazol inhibited plant height and leaf size in Lilium Longiflorum-Asiatic hybrid, and then RNA-Seq technique was employed to analyze gene transcripts of Lilium Longiflorum-Asiatic hybrid leaves by paclobutrazol treatment in order to get a deeper insight into dwarfism mechanism of lily. Approximately 38.6 Gb data was obtained and assemble into 53,681 unigenes. Annotation, pathways, functional classification and phylogenetic classification of these data were analyzed based on Nr, Nt, Swiss-Prot, KEGG, COG and GO databases. 2,704 differentially expressed genes were screened by comparing paclobutrazol-treated samples with untreated samples and quantitative real-time PCR was performed to validate expression profiles. By analyzing dynamic changes of differentially expressed genes, nine metabolic pathways and signal transduction pathways were significantly enriched and many potentially interesting genes were identified that encoded putative regulators or key components of cell division, cell expansion, GA metabolism and signaling transduction and these genes were highlighted to reveal their importance in regulation of plant size. These results will provide a better understanding of the molecular mechanism on lily dwarfism and some potential genes related to lily organ size, which will lay the foundation for molecular breeding of potted lilies. These transcriptome data will also serve as valuable public genomic resources for other genetic research in lily.